The Charismatic Leadership and Exercise of Administrative Authority in Bangkok, 2022, Mr. Chatchat Sitthipanth - Naronglidach, Vatchara; Pukkeeree, Peerapong; Thummachote, Ravipa (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: Bangkok has had administrators in the political arena who are tied to traditional thinking, emphasizing working within the framework of authoritative power. However, with the recent election, the public seeks a new leader with fresh perspectives and a new approach to governance. Mr. Chatchat Sittiphan possesses the qualities that align with the desired change, making him the chosen candidate for the position of Governor of Bangkok. In this thesis aims; (1) To study the relationship between charismatic leadership and the exercise of administrative authority in Bangkok in the year 2022, Mr. Chatchat Sitthipan conducted research. And (2) To investigate the factors of charismatic leadership that influence the exercise of administrative authority in Bangkok. Methodology: In this research, the sample group consists of 400 residents from the 50 districts of Bangkok. The data collection instrument utilized is a questionnaire with a confidence level of 0.978. The statistical methods employed for data analysis include frequency distribution, percentage, mean, standard deviation, Pearson's product-moment correlation coefficient analysis, and multiple regression analysis. Results: 1) The relationship between charismatic leadership and the exercise of authority in managing Bangkok at a statistically significant level of 0.01 and 2) Factors of charismatic leadership influencing the exercise of authority in managing Bangkok at a statistically significant level of 0.01 Conclusion: Statistically significant findings at a significance level of 0.01 show that charismatic leadership has a significant impact on authority in managing Bangkok, highlighting its important role in governance and decision-making processes within the city.